1997
DOI: 10.1302/0301-620x.79b2.7167
|View full text |Cite
|
Sign up to set email alerts
|

Triple Osteotomy Of The Pelvis For Acetabular Dysplasia: Results At 8 To 15 Years

Abstract: Reorientation of the acetabulum may be required in adolescents and young adults with developmental dysplasia of the hip. We have carried out a retrospective 5,6 results of these procedures/' Although most authors argue that they reduce the risk of secondary degenerative arthri tis,7 this has never been demonstrated in clinical studies.review of 51 hips after triple osteotomy with an average We have reviewed 51 hips at between 8 and 15 years after follow-up of ten years (8 to 15). Forty-eight hips (94%) were av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 15 publications
5
68
3
Order By: Relevance
“…4). Compared with the literature, Group I in the current study showed a superior survivorship rate of 90% at 10 years followup (Table 5) [5,11,17,21,26,33,44,48]. Reported survivorship rates for PAO ranged from 54% to 85% [11,17,21,33].…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…4). Compared with the literature, Group I in the current study showed a superior survivorship rate of 90% at 10 years followup (Table 5) [5,11,17,21,26,33,44,48]. Reported survivorship rates for PAO ranged from 54% to 85% [11,17,21,33].…”
Section: Discussioncontrasting
confidence: 48%
“…Reported survivorship rates for PAO ranged from 54% to 85% [11,17,21,33]. For triple and Chiari osteotomies, the reported survival rates at 10 years followup were 73% and 84%, respectively (Table 5) [5,26]. The survivorship rate in our Group II, including hips with morphologic features predisposing to FAI, was 78% and was at the lower range of the reported rates in the literature (Table 5).…”
Section: Discussionmentioning
confidence: 65%
“…We present a series of patients with a followup of 96% at 23 to 29 years after pelvic osteotomies. This study is a followup study after previous reports on the 8-to 15-year follow-up and a 15-year followup of triple osteotomies of the pelvis [5,22]. The purposes of this study therefore were to determine whether the triple osteotomy can provide (1) continuing pain relief and (2) function; and to determine the (3) incidence of OA and (4) number of patients undergoing THA 23 years or more after triple osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The operative technique has been described previously [5,11]. The operation began with a separate posterior approach for the osteotomy of the ischium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation